Teachers Procedures Related to Students Misbehaviour in the Physical Education Lesson - Oliveira, Maria Teresa Mateus (2013)
Abstract Introduction Misbehaviour in schools and in the classroom is considered to be a serious problem to all those interested in the problematic of teaching. Teachers tend to attribute the cause for misbehaviour, more to external factors (students personal characteristics, rudeness and parent alienation, problematic family environment), than to internal ones. Material and Methods The study involved 12 PE teachers, divided into 3 different groups, and 1050 students of 48 classes in the 6th, 7th and 8th grades. Data was collected using an observation system of students misbehaviour [1], and the Physical Education Pupil Control Inventory (PEPCI) [2]. Finally, all the data was analyzed using descriptive and GLM Repeated Measures statistics.